2021
DOI: 10.29271/jcpsp.2021.06.651
|View full text |Cite
|
Sign up to set email alerts
|

Initial Ca 125 Value as a Predictive Marker for High-grade Serous Ovarian Cancer

Abstract: Objective: To determine the relevance between the cut-off level of cancer antigen 125 (CA 125) level and long-term prognosis in high-grade serous ovarian cancer (HGSCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The disease progression and regression can be predicted nearly in 90% of cases with variation in serum levels of CA-125. 7,21 In the present study, 80% patients were chemosensitive while 20% showed resistance to chemotherapy. In a study by Zheng et al, 2021 5 out of 60 OC patients 44 (73.33%) were chemo-sensitive while 16 (26.67%) showed chemo-resistance.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…The disease progression and regression can be predicted nearly in 90% of cases with variation in serum levels of CA-125. 7,21 In the present study, 80% patients were chemosensitive while 20% showed resistance to chemotherapy. In a study by Zheng et al, 2021 5 out of 60 OC patients 44 (73.33%) were chemo-sensitive while 16 (26.67%) showed chemo-resistance.…”
Section: Discussionsupporting
confidence: 48%
“…4,5 Serous ovarian carcinoma (SOC) makes up the most common histological subtype of EOCs and is divided into High grade serous ovarian carcinoma (HGSOC) and Lowgrade serous ovarian carcinoma (LGSOC). 6,7 Extensive cytoreductive surgery combined with platinum-based chemotherapy is currently the standard treatment for most of the patients without consideration of individual prognostic and predictive biomarkers. Firstline platinum chemotherapy is highly effective but unfortunately more than 80% of patients relapse and become platinum-resistant.…”
mentioning
confidence: 99%
“…We analyzed the data from 6063 EOC cancer patients in 17 studies ( 6 , 14 , 15 , 17 19 , 23 , 24 , 26 , 27 , 30 36 ) to determine the relationship between pretreatment serum CA-125 level and OS. A random-effects model was employed based on the results of the heterogeneity analysis (I 2 = 86.40%, p <0.001).…”
Section: Resultsmentioning
confidence: 99%
“…CA 125, encoded by the homonymous MUC16 gene, is a glycoprotein that constitutes a significant part of mucus, offering protection against pathogens to the surfaces of different organs (such as the lungs, pleura, peritoneum, endometrium, and endocervix) and is primarily linked to ovarian cancer [61,62].…”
Section: Ca 125mentioning
confidence: 99%